2014
DOI: 10.1007/s11033-014-3566-y
|View full text |Cite
|
Sign up to set email alerts
|

In tobacco BY-2 cells xyloglucan oligosaccharides alter the expression of genes involved in cell wall metabolism, signalling, stress responses, cell division and transcriptional control

Abstract: In tobacco BY-2 cells xyloglucan oligosaccharides alter the expression of genes involved in cell wall metabolism, signalling, stress responses, cell division and transcriptional control.--Manuscript Draft--

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Xyloglucans are the most common hemicelluloses in dicot primary cell walls but they are scarce in monocots [64]. The primary function of xyloglucan is the formation of a network with cellulose microfibrils in the cell walls but some reports have also demonstrated its role in cell signalling [65] and as a storage material in seeds [63]. Our work demonstrated that the hemicellulose that is recognised by the LM25 antibodies (for xyloglucan) was present in the cell walls and the antibody that was used for its detection gave the most abundant signals among all of the antibodies that were used.…”
Section: Discussionmentioning
confidence: 99%
“…Xyloglucans are the most common hemicelluloses in dicot primary cell walls but they are scarce in monocots [64]. The primary function of xyloglucan is the formation of a network with cellulose microfibrils in the cell walls but some reports have also demonstrated its role in cell signalling [65] and as a storage material in seeds [63]. Our work demonstrated that the hemicellulose that is recognised by the LM25 antibodies (for xyloglucan) was present in the cell walls and the antibody that was used for its detection gave the most abundant signals among all of the antibodies that were used.…”
Section: Discussionmentioning
confidence: 99%
“…A less well‐characterized wall fragment is xyloglucan oligosaccharide (XGO). Tobacco BY‐2 (cv Bright Yellow 2) cell cultures treated with XGO exhibit an increase in fresh weight and an up‐regulation of genes related to abiotic and biotic stresses (González‐Pérez et al ., ), but whether XGO acts as a signal in growth regulation and stress response warrants further investigation.…”
Section: Cell Wall Integrity Sensingmentioning
confidence: 99%
“…Previous studies indicated that Xh may play a role in the regulation of plant growth and development in different plant species ( Fry et al, 1993 ; Vargas-Rechia et al, 1998 ). Indeed, treatment with Xh of tobacco cell cultures and whole plants results in accelerated cell elongation and division, changes in primary root growth, and upregulation of defense-related gene expression ( González-Pérez et al, 2014 ). Moreover, Xh can increase plant resistance to abiotic stress, in particular cold or water stress, when used at low concentrations ( Salvador and Lasserre, 2010 ).…”
Section: Introductionmentioning
confidence: 99%